2012
DOI: 10.1134/s002689331205010x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous CD38 expression in tumor tissues of patients with colorectal cancer

Abstract: The CD38 gene encodes a membrane bound protein that takes part in cell adhesion and catalyzes the formation of cyclic ADP ribose. The presence of the full size and alternative forms of CD38 mRNA in tumor tissue specimens from patients with colorectal cancer and tumor cell lines was analyzed by RT PCR. It was shown that tumor specimens contained cells that constantly express CD38; full size CD38 mRNA was detected more frequently than its alternative form. CD38 mRNA was found in Colo 205, T 84, HCT15, and HCT116… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…At the same time, the results of IHC showed that there was a 40% (12/30) high score of CD38 in cervical cancer tissues and 16.6% (5/30) in the adjacent non-cancerous tissues (p= 0.02<0.05). Perenkov et al (35) found that the expression of the CD38 gene is heterogeneous in the tumor cells of patients with colorectal cancer. CD38 expression is triggered at least in part by a certain cytokine(s) secreted by cancer cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the results of IHC showed that there was a 40% (12/30) high score of CD38 in cervical cancer tissues and 16.6% (5/30) in the adjacent non-cancerous tissues (p= 0.02<0.05). Perenkov et al (35) found that the expression of the CD38 gene is heterogeneous in the tumor cells of patients with colorectal cancer. CD38 expression is triggered at least in part by a certain cytokine(s) secreted by cancer cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Whether in cancer biology this enzymatic activity is important has never been ascertained. On the other hand, as a receptor, CD38 is responsible of T cell activation, in particular in lamina propria cells, promoting colitis (Lischke et al, 2013) and it has been considered a positive prognostic marker for CRC (Perenkov et al, 2012). Karakasheva et al have highlighted that CD38 might be an interesting target for metastatic CRC.…”
Section: Therapeutic Role Of Cd38 Inhibitors/ Antibodies In Colorectal Cancermentioning
confidence: 99%